Feasibility study of in vitro drug sensitivity assay of advanced non-small cell lung adenocarcinomas - Emoke Papp; Anita Steib; Elhusseiny MM Abdelwahab; Judit Meggyes-Rapp; Laszlo Jakab; Gabor Smuk; Erzsebet Schlegl; Judit Moldvay; Veronika Sárosi; Judit E Pongracz (BMJ Open Respiratory Research)
Background Despite improved screening techniques, diagnosis of lung cancer is often late and its prognosis is poor. In the present study, in vitro chemosensitivity of solid tumours and pleural effusions of lung adenocarcinomas were analysed and compared with clinical drug response.Methods Tumour cells were isolated from resected solid tumours or pleural effusions, and cryopreserved. Three-dimensional (3D) tissue aggregate cultures were set up when the oncoteam reached therapy decision for individual patients. The aggregates were then treated with the selected drug or drug combination and in vitro chemosensitivity was tested individually measuring ATP levels. The clinical response to therapy was assessed by standard clinical evaluation over an 18 months period.Results Based on the data, the in vitro chemosensitivity test results correlate well with clinical treatment response.Conclusions Such tests if implemented into the clinical decision making process might allow the selection of an even more individualised chemotherapy protocol which could lead to better therapy response.